Mothers and fathers of autistic children an exploratory study of family stress and coping - Liwag, Ma. Emma Concepcion D. ([Metro Manila] Psychological Association of the Philippines, 1989)
Thirteen mothers and 12 fathers participated in two phases ofa study that explored the stress and coping experiences offamilies ofautistic children undergoing therapy. In the first phase. the parents responded to a three-part questionnaire that assessedfamily and parental demographic characteristics. In the second phase, a semi-projective test, the Sentence Completion Form (SCF), and in-depth interviews elicited parents' emotional reactions towards the auiistic child and altitudes towards the handicap. Only the SCF data is reported in this paper. Content analysis of the parents' completions revealed that families were most stressed by the defects and disabilities associated with au/ism itself. including lack of speech, hyperactivity, and tantrum behavior. A second SOUTce of stress is the permanence ofthe child's condition and the anxiety that the child will never be normal. Two forms of family coping were identified-i-instrumental adjustments so that the autistic child becomes the focal point offamily life; and emotional acceptance of the child and the handicap. The stress and coping data were hypothesized to resemble Farber's concept ofa "tragic crisis" typical ofhigh and middle SES parents' response to a child's abnormality.
Includes bibliographical references(page 16)
Keywords: Psychology Philippines -- Periodicals